Investigation into the Impact of Mutual Coupling on the Performance of a Multiuser MIMO System Employing Generalized Channel Inversion Technique - Feng Wang; Konstanty Bialkowski; Marek E. Bialkowski (International Journal of Antennas and Propagation)
In this paper, the performance of generalized channel inversion (GCI) technique for a multiuser MIMO system operating under antenna mutual coupling conditions is investigated. The investigation is performed via theoretical derivations and computer simulations. The theoretical derivations show that the presence of mutual coupling may result in an increased performance in terms of sum rate capacity. The simulation experiments confirm the theoretical findings in examples of three groups of numerical results. These results show that the existence of mutual coupling in an array antenna at base station (BS) results in an increased sum rate capacity when antenna interelement spacing at BS is smaller than 0.55 λ. Also it is shown that the presence of mutual coupling at mobile user (MS) terminals results in an increased sum rate capacity when antenna inter-element spacing at MSs is smaller than 0.4 λ. When mutual coupling is considered at both BS and MSs, the system configuration with antenna inter-element spacing equal to 0.45 λ at BS and 0.4 λ at MSs leads to the highest sum rate capacity.